Meta-modelo para o processo de sistemas com RV pautado por enfoque no usuário, iteratividade de projeto e critérios de usabilidade - Olher, Milena Marquezin (Universidade Federal de São Carlos, 2004)
The continuous growth of the Human-Computer Interaction area has been causing the appearance of approaches to better correspond to the users' needs, concerning not only the functionality factors of the interactive systems, which are the main focus of the Software Engineering area, but also the interaction factors of those systems. In that context, the Virtual Reality technology comes as a change proposal for the development of more advanced interfaces, with regard to the human-computer interaction, offering means of interaction that are more natural to humans to supply to the interactive system users' expectations by a more natural and intuitive interaction, as well as involving resources and studies in the most several fields of the knowledge. In that way, although it has evolved significantly, its usage in interactive systems still presents challenges to overcome, among which a better analysis and formalization of the process of systems with Virtual Reality in the practices of the Human-Computer Interaction and Software Engineering areas. However, researches that detail the process of systems with Virtual Reality so that its benefits are explored are little found in the literature. This work proposes a meta-model for the process of systems with Virtual Reality, identifying the differential of those systems and the existing implications in your process, presenting and critically analyzing the methodologies mentioned in the literature for the process of systems with Virtual Reality, as well as identifying the process models in Software Engineering and the approaches in Human-Computer Interaction that best assist the identified implications in the process of those systems, which focus on the user, project iteration and usability.
Keywords: Engenharia de software; Interação homem-máquina; Realidade virtual; Processo de desenvolvimento para ambientes virtuais; Usabilidade; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO